Followers' Motives as Moderators of the Effects of Transformational Leadership Behaviors on Follower Outcomes and Leaders' Influence - Hugo M. Kehr; Dorena Graff; Cafer Bakaç (Journal of Business and Psychology, 2022)
The present paper reports three studies that were based on the general proposition that the effectiveness of transformational leadership (TL) depends on whether the displayed TL behaviors match the followers' motives. Specifically, inspirational motivation should be effective with followers high on the power motive, intellectual stimulation should be effective with followers high on the achievement motive, and individual consideration should be effective with followers high on the affiliation motive. In study 1, in order to confirm the hypothesized conceptual relationships between TL and motives, we systematically analyzed the TL literature ( N 0.167em=0.167em139 papers) for motive content and found, as predicted, that descriptions of inspirational motivation, intellectual stimulation, and individual consideration were associated with power, achievement, and affiliation motive content, respectively. Study 2, a vignette study, confirmed that participants' ( N 0.167em=0.167em113) motives determined their preferences for the respective TL behaviors. In study 3 ( N 0.167em=0.167em116), we manipulated TL behaviors with video clips and confirmed the predictions that followers' affiliation [power] motive moderated the effects of individual consideration [inspirational motivation] on leaders' influence and followers' task performance. Mixed results were obtained regarding the expected moderating function of followers' achievement motive on the effects of intellectual stimulation. Findings are discussed with respect to their importance in establishing TL as a motivation theory.
Keywords: 650; Transformational leadership behaviors; Follower motives; Individual consideration; Inspirational motivation; Intellectual stimulation; Leadership effectiveness